2010
DOI: 10.1080/10934529.2010.486310
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation of naphthenic acids mixtures by lake biofilms

Abstract: The dissipation (combined sorption and biodegradation) of naphthenic acids (C(n)H(2n+z)O(2)) by lake biofilms with no previous adaptation to oil sands acids was investigated using rotating annular bioreactors. The dissipation by the biofilm was dependent on the chemical composition of the naphthenic acids mixture. There were 2 distinct groups of Fluka naphthenic acids which dissipated with pseudo first order kinetics: (a) t(1/2)= 7 days, r(2)= 0.984 and (b) components which were less readily dissipated with t(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Aside from even numbered carboxylic acid functional groups, studies have shown that alkyl side chain branching hinders NA degradation ( Herman et al, 1993 ; Smith et al, 2008 ; Johnson et al, 2011 ; Huang et al, 2012 ), as well as an increase the degree of cyclicity (ring cleavage is energetically costly) and molecular weight ( Scott et al, 2005 ; Han et al, 2008 ; Toor et al, 2013 ; Misiti et al, 2014 ). Other recalcitrant NAs include non-classical NAs, such as those containing elements of S or N ( Headley et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aside from even numbered carboxylic acid functional groups, studies have shown that alkyl side chain branching hinders NA degradation ( Herman et al, 1993 ; Smith et al, 2008 ; Johnson et al, 2011 ; Huang et al, 2012 ), as well as an increase the degree of cyclicity (ring cleavage is energetically costly) and molecular weight ( Scott et al, 2005 ; Han et al, 2008 ; Toor et al, 2013 ; Misiti et al, 2014 ). Other recalcitrant NAs include non-classical NAs, such as those containing elements of S or N ( Headley et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…The biodegradability of NAs by OSPW microorganisms has been explored and reviewed extensively ( Clemente and Fedorak, 2005 ; Quagraine et al, 2005 ; Allen, 2008b ; Kannel and Gan, 2012 ), but no one particular method to harness the naturally occurring microbes for use in ex situ NA treatment has been established and put into practice. One potential strategy that has been proposed and evaluated in a limited number of studies is the use of microbial biofilms in ex situ bioreactors targeting NA bioremediation ( Headley et al, 2010 ; Huang et al, 2012 ; Gunawan et al, 2014 ; McKenzie et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of recalcitrant compounds could be one of the main factors inhibiting further biodegradation (Taylor and Trudgill, 1978;Rontani and Bonin, 1992;Quagraine et al, 2005b). In addition, current research indicated that the performance of biodegradation could be improved by increasing biomass concentration and microbial activity (Headley et al, 2010;Misiti et al, 2013). Therefore, besides carbon source, inorganic macronutrients such as nitrogen (N) and phosphorus (P) are also needed to facilitate bacterial growth.…”
Section: Biodegradation Of Organic Compounds After Ozonationmentioning
confidence: 97%
“…Headley et al (2010) applied rotating annular bioreactors with lake biofilm and no dissipation was evident when exposing to OSPW naphthenic acids. However, commercial NAs (Fluka naphthenic acids) could be found with dissipation.…”
Section: Comparisons Of Bioreactor Ospw Treatmentmentioning
confidence: 98%
“…Headley et al (2010) evaluated the potential of biofilm development in a rotating annular bioreactor using lake water. However, little impact on the degradation of OSPW NAs was achieved.…”
Section: Introductionmentioning
confidence: 99%